2015
DOI: 10.11152/mu.2013.2066.172.usev
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic evaluation of the posterolateral radiohumeral plica in asymptomatic subjects and patients with osteoarthritis.

Abstract: Aims: The aim of this study was to describe the morphological features of posterolateral radiohumeral (RH) plica in asymptomatic subjects and in patients with elbow osteoarthritis using ultrasonography (US). Material and methods: The control group included a total of 100 healthy elbows (51 subjects) and the study group consisted of 22 elbows (22 patients) with osteoarthritis confirmed clinically and by imaging methods. The presence, length, height, thickness, cross sectional area, shape, and echogenicity of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…OA affects mainly the radiohumeral joint, where US allows for the humeral and radial cartilage thickness measurement with a mean of 1.2 mm, showing significantly reduced values in OA [41]. Also, the posterolateral radiohumeral plica may be evaluated, showing that OA may result in plica reduction associated with morphological changes [41]. In addition, lateral synovial fringe impingement at the radiohumeral joint may be assessed [42,43].…”
Section: Clinical Applicationmentioning
confidence: 99%
“…OA affects mainly the radiohumeral joint, where US allows for the humeral and radial cartilage thickness measurement with a mean of 1.2 mm, showing significantly reduced values in OA [41]. Also, the posterolateral radiohumeral plica may be evaluated, showing that OA may result in plica reduction associated with morphological changes [41]. In addition, lateral synovial fringe impingement at the radiohumeral joint may be assessed [42,43].…”
Section: Clinical Applicationmentioning
confidence: 99%
“…6a ). 16 , 33 The ultrasound scan may also exclude other pathologies such as tendinopathy, loose bodies, impinging osteophytes and snapping triceps. Finally, the elbow arthroscopy allows for a direct visualization anteriorly and posteriorly as well as the dynamic evaluation of the plica for final confirmations ( Fig.…”
Section: Imagingmentioning
confidence: 99%
“…From a structural point of view, RHSP are folds that project into the intermediate radiohumeral space contiguous with the capsule-ligament complex [20], found proximal to the edge of the annular ligament within the intra-articular space [12,15,19,20]. They are structurally distinct from the annular ligament since they are contiguous with the radio-humeral articular capsule and subtly mingle with the common extensor tendon forming an enthesis at the lateral epicondyle [12].…”
Section: Anatomymentioning
confidence: 99%
“…Ultrasound scans have demonstrated that RHSP in asymptomatic patients can be assessed in a reliable way; the advantage is that this is a non-invasive procedure that involves little or no risk for these patients [15,22,25]. In ultrasound images, the morphology of RHSP is described as a triangular structure surrounded by hypoechoic borders between the capitellum and the radial head and isoechoic with muscles shown as a consistent structure, distinct from other periarticular structures [15,25]. There is no correlation between the real size of RHSP and the mean size in ultrasound images according to Koh et al [25].…”
Section: Imaging Diagnosismentioning
confidence: 99%
See 1 more Smart Citation